Performance Assessment of Village Apparatus in Population Administration Services - Khirom, Zitni Syifa’al; Mursyidah, Lailul (Indonesian Journal of Cultural and Community Development, 2024)
The general background of this research highlights the importance of village apparatus performance in population administration services as a key factor in enhancing efficiency and accessibility of services for the community. The specific background focuses on the analysis of the performance of the Sumberejo Village apparatus in Sidoarjo, selected for its relevance as a representation in assessing service quality. The knowledge gap identified in this study pertains to the lack of comprehensive evaluation regarding productivity, service quality, and accountability in the context of administrative services. The aims of the research are to evaluate the performance of village apparatus in providing services and to offer recommendations for improvement. The results reveal that the performance of the village apparatus is inadequate, with productivity indicators showing good mental attitudes but lacking in technological understanding and work discipline. Service quality is also assessed as insufficient, as indicated by lengthy and complicated service times, resulting in criticism from the community. The novelty of this study lies in its qualitative descriptive analysis that explores practical challenges faced by local administrators. The implications of these findings suggest that improving technological understanding, work discipline, and streamlining service processes are essential for enhancing the quality of administrative services and meeting community expectations. Highlights: Analysis reveals inadequate performance in service delivery by village apparatus. Lack of technological proficiency among village staff affects service efficiency. Lengthy and complicated service processes lead to negative feedback from the community. Keywords: Performance, Service, Productivity, Quality, Accountability